Development of learning video rotation using Palembang tanjak context to determine students’ mathematical reasoning - Hasanah, Uswatun; Putri, Ratu Ilma Indra; Zulkardi (Universitas Hamzanwadi, 2024)
This research is essential as a starting point in using learning videos on rotation material assisted by the Palembang tanjak context so that students' mathematical reasoning abilities are good. This research aims to produce a learning video on rotation material using the Palembang tanjak context that is valid and practical, as well as to determine the potential effect of using videos on rotation material using the Palembang tanjak context on students' mathematical reasoning ability. PMRI and collaborative learning approaches were also used in this research. This type of research is a design research type of development studies. The subjects of this study involved 28 students of class IX.A. Data collection techniques were observation, tests, and interviews. The data analysis technique is descriptive. This research resulted in a learning video on rotation material using the context of Palembang tanjak, which was developed to be valid and practical and potentially affected students' mathematical reasoning ability with an average of 67.625. Learning videos on rotation material can be used to train students' mathematical reasoning skills within the Palembang Tanjak context.